Justification of an administrative decision issued by means of an artificial intelligence system in the light of the principle of fostering trust in public authorities (Discourse of Law and Administration, 2025)
A crucial element of a decision is its justification, which is of great importance for the implementation of the principle of enhancing the authority’s confidence in the state, in particular by making the addressee of the decision believe that his or her claims have been taken into account in the determination of the case. The ongoing automation of various public administration activities makes the authorities increasingly use artificial intelligence systems. Integrating such solutions into the sequence of actions taken by the authority must consider the principles of administrative proceedings. This paper aims to analyse the requirements to justify an administrative decision issued with the help of an artificial intelligence system considering the implementation of the principle of building trust in public authority. It will be examined whether the explanation by the authority of the principles of the artificial intelligence system in the justification of the decision is necessary to implement this principle.
Keywords: artificial intelligence; explainability; statement of reasons; automation